Generative Face from Random Data, on ‘How Computers Imagine Humans’ - Moura, João Martinho (2018)
In the recent years, face detection technologies have been widely used by artists to create digital art. Face detection provides new forms of interaction, and allows digital artefacts to detect the presence of human beings, through video capture and facial detection, in real-time. In this paper we explore the algorithm proposed by Paul Viola and Michael Jones, presented in 2001, in order to generate imagined faces from visual randomness.